2007
DOI: 10.1007/s10637-007-9096-x
|View full text |Cite
|
Sign up to set email alerts
|

A novel quinoline, MT477: suppresses cell signaling through Ras molecular pathway, inhibits PKC activity, and demonstrates in vivo anti-tumor activity against human carcinoma cell lines

Abstract: MT477 is a novel thiopyrano[2,3-c]quinoline that has been identified using molecular topology screening as a potential anticancer drug with a high activity against protein kinase C (PKC) isoforms. The objective of the present study was to determine the mechanism of action of MT477 and its activity against human cancer cell lines. MT477 interfered with PKC activity as well as phosphorylation of Ras and ERK1/2 in H226 human lung carcinoma cells. It also induced poly-caspase-dependent apoptosis. MT477 had a dose-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 33 publications
1
33
1
Order By: Relevance
“…Together, these observations reinforce the notion that PKC-dependent Ser181-phosphorylation of oncogenic KRAS is required for tumorigenesis. This effect may account for the previously reported inhibition of different KRAS-driven tumor xenografts by PKC pharmacologic inhibition (30,33,34). Interestingly, it has also been shown that PKCd knockdown prevents apoptosis and promotes tumorigenesis in cells addicted to aberrant KRAS signaling (35)(36)(37).…”
Section: Pkc Inhibitors Diminish Oncogenic Kras-mediated Tumor Growthmentioning
confidence: 66%
“…Together, these observations reinforce the notion that PKC-dependent Ser181-phosphorylation of oncogenic KRAS is required for tumorigenesis. This effect may account for the previously reported inhibition of different KRAS-driven tumor xenografts by PKC pharmacologic inhibition (30,33,34). Interestingly, it has also been shown that PKCd knockdown prevents apoptosis and promotes tumorigenesis in cells addicted to aberrant KRAS signaling (35)(36)(37).…”
Section: Pkc Inhibitors Diminish Oncogenic Kras-mediated Tumor Growthmentioning
confidence: 66%
“…Furthermore, our research group has cover a long way in the topological design of new drugs [28][29][30].…”
Section: Resultsmentioning
confidence: 99%
“…Other evidence has demonstrated that these kinds of structures, like the well known quinoline analog MT477, suppress cell signaling through Ras molecular pathway, inhibiting PKC activity. The effect of this compound is dose-dependent on H226, MCF-7, U87, LNCaP, A431 and A549 cancer cell lines [17]. Two murine xenograft models of human A431 and H226 lung carcinoma were used also to evaluate tumor response to intraperitoneal administration of MT477.…”
Section: Introductionmentioning
confidence: 99%